Understanding mangrove governance: Research methods and guidelines - Pham Thu Thuy; Mwangi, E.; Vu, T.P.; Hoang, T.L. (Center for International Forestry Research, 2022)
Mangrove governance requires cross-sectoral and multistakeholder collaboration. Effective mangrove management also requires institutional setup, rules of the game, and a clear tenure regime and distribution of rights and responsibilities between stakeholders. The outcomes of mangrove protection and conservation will be different under different mangrove management regimes (state-owned, community-led initiatives, private sector-led initiatives, co-management between the state and local communities, or public-private partnerships). Understanding the complexities of mangrove governance is challenging and requires appropriate research methods.